2007
DOI: 10.1007/s10495-007-0137-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β enhances the effect of serum deprivation on rat annular cell apoptosis

Abstract: Excessive apoptosis of disc cells is believed to play an important role in intervertebral disc (IVD) degeneration. It has been shown that interleukin-1beta (IL-1beta) is involved in the failure of disc matrix by suppressing the synthesis of matrix components and stimulating the expression of matrix metalloproteinases. However, whether IL-1beta induces disc cell apoptosis is still unclear. The objective of this study was to investigate the effect of IL-1beta on the apoptosis of rat annular cells cultured with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 46 publications
(60 reference statements)
2
52
0
Order By: Relevance
“…Our established method for isolation and primary culture of rat annular cells (Zhao et al 2007) was employed, and first-passage cells maintained in a monolayer were used throughout the in vitro experiments.…”
Section: Isolation and Culture Of Rat Annular Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our established method for isolation and primary culture of rat annular cells (Zhao et al 2007) was employed, and first-passage cells maintained in a monolayer were used throughout the in vitro experiments.…”
Section: Isolation and Culture Of Rat Annular Cellsmentioning
confidence: 99%
“…1 Cross-talk between mitochondria and ER in NO-induced apoptosis. Contents shown in italic type within the diagram were studied Pharmingen), as described previously (Zhao et al 2007). …”
Section: Apoptosis Detection By Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…46 (Table 1) Although the means (intrinsic or extrinsic to the disc environment) that lead to deregulation in the production of IL-1β and TNF-α have not yet been elucidated, these are known to be related to the increase of matrix degrading enzymes, abnormal synthesis of aggrecan and type II collagen, besides its substitution by type I, angiogenesis, axonogenesis and apoptosis of IVD cells. 19,[50][51][52][53] …”
Section: Action Of Proinflammatory Cytokines On the Intervertebral Discmentioning
confidence: 99%
“…Serum also enables the maintenance of optimal pH and the elimination of the toxic products from the medium (9). Serum deprivation is one of many methods used to induce programmed cell death, or apoptosis (17,18,19). Previous research has demonstrated that cells in serum-deprived media undergo numerous changes that lead to apoptosis.…”
Section: Introductionmentioning
confidence: 99%